Elbasvir/grazoprevir and sofosbuvir for hepatitis C virus genotype 3 infection with compensated cirrhosis: A randomized trial. Issue 6 (19th April 2018) - Foster, Graham R.; Agarwal, Kosh; Cramp, Matthew E.; Moreea, Sulleman; Barclay, Stephen; Collier, Jane; Brown, Ashley S.; Ryder, Stephen D.; Ustianowski, Andrew; Forton, Daniel M.; Fox, Ray; Gordon, Fiona; et al.
Abstract : Many direct‐acting antiviral regimens have reduced activity in people with hepatitis C virus (HCV) genotype (GT) 3 infection and cirrhosis. The C‐ISLE study assessed the efficacy and safety of elbasvir/grazoprevir (EBR/GZR) plus sofosbuvir (SOF) with and without ribavirin (RBV) in compensated cirrhotic participants with GT3 infection. This was a phase 2, randomized, open‐label study. Treatment‐naive participants received EBR/GZR + SOF + RBV for 8 weeks or EBR/GZR + SOF for 12 weeks, and peginterferon/RBV treatment‐experienced participants received EBR/GZR + SOF ± RBV for 12 weeks or EBR/GZR + SOF for 16 weeks. The primary endpoint was HCV RNA <15 IU/mL 12 weeks after the end of treatment (sustained virologic response at 12 weeks [SVR12]). Among treatment‐naive participants, SVR12 was 91% (21/23) in those treated with RBV for 8 weeks and 96% (23/24) in those treated for 12 weeks. Among treatment‐experienced participants, SVR12 was 94% (17/18) and 100% (17/17) in the 12‐week arm, with and without RBV, respectively, and 94% (17/18) in the 16‐week arm. Five participants failed to achieve SVR: 2 relapsed (both in the 8‐week arm), 1 discontinued due to vomiting/cellulitis (16‐week arm), and 2 discontinued (consent withdrawn/lost to follow‐up). SVR12 was not affected by the presence of resistance‐associated substitutions (RASs). There was no consistent change in insulin resistance, and 5 participants reported serious adverse events (pneumonia, chest pain, opiate overdose, cellulitis, decreased creatinine). High efficacy was demonstrated in participants with HCV GT3 infection and cirrhosis. Treatment beyond 12 weeks was not required, and efficacy was maintained regardless of baseline RASs. Conclusion : Data from this study support the use of EBR/GZR plus SOF for 12 weeks without RBV for treatment‐naive and peginterferon/RBV–experienced people with GT3 infection and cirrhosis (ClinicalTrials.gov NCT02601573). (Hepatology 2018;67:2113‐2126)